2021
DOI: 10.1177/17588359211018028
|View full text |Cite
|
Sign up to set email alerts
|

Osimertinib rechallenge under steroid protection following osimertinib-induced pneumonitis: three case studies

Abstract: Osimertinib is a third-generation tyrosine kinase inhibitor that became the preferred first-line treatment option for metastatic non-small cell lung cancer with sensitizing epidermal growth factor receptor mutations. Drug-induced pneumonitis is known to occur with osimertinib. In case of severe pneumonitis, discontinuation of treatment and therapy with corticosteroids is recommended, and a treatment switch is usually performed. We herein report the treatment course in three patients who were rechallenged with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Therefore, timely intervention is very important. The majority of reported cases, including our case, successfully controlled OsiILD by discontinuing or reducing osimertinib and treating it with corticosteroids [ 5 , 15 , 27 , 28 , 30 , 32 35 , 37 , 38 ]. It has also been reported that OsiILD can be successfully controlled by nintedanib [ 36 ], so the use of nintedanib to control OsiILD can be considered in patients who are not suitable for corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Therefore, timely intervention is very important. The majority of reported cases, including our case, successfully controlled OsiILD by discontinuing or reducing osimertinib and treating it with corticosteroids [ 5 , 15 , 27 , 28 , 30 , 32 35 , 37 , 38 ]. It has also been reported that OsiILD can be successfully controlled by nintedanib [ 36 ], so the use of nintedanib to control OsiILD can be considered in patients who are not suitable for corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 96%
“…In several cases about OsiILD reported so far, most of the patients had risk factors, such as advanced age, contralateral lung metastasis, use of nivolumab and so on [3,5,15,[27][28][29][30][31][32][33][34][35][36][37][38]. The patient we reported was an elderly woman with contralateral lung metastasis, PS was grade 2, and she developed grade 3 ILD with acute lung injury after 3 months of treatment with osimertinib.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations